Perlindungan Hukum kepada Anak terhadap Kejahatan Pelecehan Seksual (SETARA : Jurnal Ilmu Hukum, 2022)
Sexual abuse against children continues to occur in society and often leaves serious psychological and developmental consequences for child victims. This article examines criminal acts and criminal sanctions for sexual abuse of minors under the Criminal Code, the Child Protection Law, and Law Number 12 of 2022 concerning Sexual Violence Crimes, and relates them to Decision No. 507/Pid.Sus/2014/PN.JKT.BAR. The study also analyzes the effectiveness of the implementation of child protection norms in providing legal protection for children. Using normative juridical research, the article finds that the applicable legal framework already provides a basis for punishment and protection, but its implementation still depends heavily on the consistency, sensitivity, and professionalism of law enforcement officers. The decision reviewed in this study reflects the use of child protection norms to affirm legal certainty and justice for child victims.